Development of Library and Information Technology Management at Mahachulalongkornrajavidyalaya University - Ragkhanto, Suwatsan; Chaiyaphan, Thanad; Pontappasan, Thanasak (Mahachula Academic Journal, 2025)
This research aimed to: (1) examine the conditions and problems of the administration of the Office of Library and Information Technology at Mahachulalongkornrajavidyalaya University, (2) investigate the opinions and needs of students and staff, and (3) propose guidelines for administrative development. A quantitative survey research design was employed. The sample consisted of 363 participants, including undergraduate and graduate students as well as staff. Data were collected through questionnaires and analyzed using descriptive statistics: percentage, mean, and standard deviation. The findings revealed that, overall, the administration of the Office of Library and Information Technology was rated at a “high” level. The personnel dimension scored the highest, followed by information resources, facilities, and services, respectively. Regarding opinions and needs, all aspects were rated highly, particularly personnel development and the provision of digital information resources. The study recommends strategic administrative development focusing on enhancing personnel competency, investing in information technology, and improving digital services to support continuous and sustainable learning for students and staff.